ANALYSIS OF THE USE OF SHARIA FINTECH REVIEWED FROM MAQASID SYARIAH IN STAI JAM'IYAH MAHMUDIYAH LANGKAT STUDENTS - Cita Ayni Putri Silalahi; Alistraja Dison Silalahi; Khairani Sakdiah; Dalmi Iskandar Sultani; Safira Khoirunnisa (CV. Barokah Publsiher, 2025)
This study aims to assess the level of understanding and use of Islamic fintech among students at STAI Jam'iyah Mahmudiyah Langkat using the perspective of maqasid sharia. The research approach used was descriptive qualitative, with data obtained through observation, interviews, and documentation. The results showed that 70% of students understood the differences between Islamic and conventional fintech, particularly in terms of avoiding usury and implementing Islamic principles. However, 30% still preferred conventional fintech due to convenience. Furthermore, approximately 80% of students used Islamic fintech services such as OVO Syariah and Dana Syariah to meet various financial needs. From the perspective of maqasid sharia, the existence of Islamic fintech contributes to safeguarding religion, life, intellect, lineage, and wealth through a halal, secure, and transparent financial system. Based on these findings, this study recommends improving education and developing technological innovations to increase interest in Islamic fintech and strengthen the application of Islamic values in the modern economic system